Newcastle disease in poultry : (Australia Centre for International Agricultural research, 1987)
Newcastle disease is the major virus disease of poultry in many countries of Southeast Asia. The results reported here will have a direct and immediate benefit to village poultry farmers and commercial enterprises in Asia